Determinants of Profitability in Nepal Oil Corporation - Shah, Gyanshyam Prasad; Pradhan, Radhe Shyam (Journal of Advanced Academic Research, 2017)
Profitability is the primary goal of all business organization. Without profitability the business will not survive in the long run. So measuring current and past profitability is very important. Profitability is measured by income and expenses where as income is generated from the activities of the business. This study aims to analyze the microeconomic and macroeconomic factors of profitability in the context of Nepal Oil Corporation. Regression analysis was used to determine the determinants of profitability. The results showed that operating cost and interest rate have a negative impact on profitability where as Gross domestic product, Inflation and size have a positive impact on profitability. This implies that the profitability of Nepal Oil Corporation depends on macroeconomic factors and microeconomic factors. The positive relationship between gross domestic product and profitability is in line with theory. Thus government policies on employment and investments should be intensified to increase the profitability of Oil Corporation. Inflation seemed to have been a positive influence on profitability; high inflation may generally be undesirable. The result suggests that probably the managers are accurately predicting inflation and are able to adjust their lending rates accordingly. Low inflationary regimes create stable economy and a congenial investment climate for business, enabling businesses to pursue long term project critical to their survival and growth.